Uang Panai: a phenomenology in determining the price of marriage - Muhammad Awal Ramadhan; Alimuddin; Ahmad Ramzi Ghulam Syam (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Uang panai a significant role in the smooth conduct of marriage. In Bugis culture, giving uang panai is an obligation in marriage. This study utilizes a systematic literature review (SLR) of several articles on uang panai in South Sulawesi. The findings of this research indicate several factors that influence the determination of uang panai, such as noble lineage, education, economy, and women's occupation. The agreement on the value of uang panai should avoid imposing excessive burdens on the groom while respecting the dignity and position of the bride, facilitated by effective communication between both parties.